Growth Differentiation Factor 15 Provides Prognostic Information Superior to Established Cardiovascular and Inflammatory Biomarkers in Unselected Patients Hospitalized With COVID-19. Issue 22 (1st December 2020) - Myhre, Peder L.; Prebensen, Christian; Strand, Heidi; Røysland, Ragnhild; Jonassen, Christine M.; Rangberg, Anbjørg; Sørensen, Vibecke; Søvik, Signe; Røsjø, Helge; Svensson, My; Erik Berdal, Jan; Omland, Torbjørn
Abstract : Background: Growth differentiation factor 15 (GDF-15) is a strong prognostic marker in sepsis and cardiovascular disease (CVD). The prognostic value of GDF-15 in coronavirus disease 2019 (COVID-19) is unknown. Methods: Consecutive, hospitalized patients with laboratory-confirmed infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and symptoms of COVID-19 were enrolled in the prospective, observational COVID Mechanisms Study. Biobank samples were collected at baseline, day 3 and day 9. The primary end point was admission to the intensive care unit or death during hospitalization, and the prognostic performance of baseline and serial GDF-15 concentrations were compared with that of established infectious disease and cardiovascular biomarkers. Results: Of the 123 patients enrolled, 35 (28%) reached the primary end point; these patients were older, more often had diabetes, and had lower oxygen saturations and higher National Early Warning Scores on baseline. Baseline GDF-15 concentrations were elevated (>95th percentile in age-stratified healthy individuals) in 97 (79%), and higher concentrations were associated with detectable SARS-CoV-2 viremia and hypoxemia (both P <0.001). Patients reaching the primary end point had higher concentrations of GDF-15 (median, 4225 [IQR, 3197–5972] pg/mL versus median, 2187 [IQR, 1344–3620] pg/mL, P <0.001). The area under the receiver operating curve was 0.78 (95% CI, 0.70–0.86). The association between GDF-15 and the primary end point persisted after adjusting for age, sex, race, body mass index, estimated glomerular filtration rate, previous myocardial infarction, heart failure, and atrial fibrillation ( P <0.001) and was superior and incremental to interleukin-6, C-reactive protein, procalcitonin, ferritin, D-dimer, cardiac troponin T, and N-terminal pro-B-type natriuretic peptide. Increase in GDF-15 from baseline to day 3 was also greater in patients reaching the primary end point (median, 1208 [IQR, 0–4305] pg/mL versus median, –86 [IQR, –322 to 491] pg/mL, P <0.001). Conclusions: GDF-15 is elevated in the majority of patients hospitalized with COVID-19, and higher concentrations are associated with SARS-CoV-2 viremia, hypoxemia, and worse outcome. The prognostic value of GDF-15 was additional and superior to established cardiovascular and inflammatory biomarkers. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04314232. Abstract : Supplemental Digital Content is available in the text.